Primary teachers` beliefs about teaching English to young learners - Roothooft, Hanne (Pulso. Revista de educación, 2017)
While there is a growing belief that English should be taught from an early age in order to achieve better results, little is known about the practices and attitudes of primary school English teachers in Spain. Therefore, a qualitative study based on interviews with 22 primary school teachers of English was carried out in order to investigate teachers’ beliefs about teaching methodology, the use of group work and the use of the mother tongue. It was found that all the teachers believe in following a communicative approach which focuses mainly on speaking and listening and in which the explicit teaching of grammar plays a minor role. Most of the teachers also claimed to use only the target language in class and to make frequent use of group and pair work. One of the aspects which seems to have influenced these teachers’ attitudes is their own negative experience as language learners in traditional, grammar-based classrooms.
Keywords: Creencias de profesores; Actitudes; Inglés como lengua extranjera; Educación primaria